1996
DOI: 10.1159/000246432
|View full text |Cite
|
Sign up to set email alerts
|

Late Cutaneous Syphilis and Neurosyphilis

Abstract: We report two syphilitic cases of indeterminable duration. The dramatic cutaneous lesions of the female patient, compatible with secondary-tertiary syphilis associated with a positive VDRL reaction in CSF together with the criteria of neurosyphilis in her male companion (despite normal TPHA and IgG indices), led us to treat both of them in an optimal way. The clinical and serological evolution was favourable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In the pre-antibiotic era, general paresis and tabes dorsalis were the most commonly recognized forms of NS [7]. During recent decades, some authors have reported changes in the clinical patterns of this disease [8,9,10,11], and these changes have generally been attributed to the expanded use of antibiotics and the growing number of patients who are coinfected with HIV. In recent years, there has been a remarkable increase in the incidence of NS in China [4].…”
Section: Introductionmentioning
confidence: 99%
“…In the pre-antibiotic era, general paresis and tabes dorsalis were the most commonly recognized forms of NS [7]. During recent decades, some authors have reported changes in the clinical patterns of this disease [8,9,10,11], and these changes have generally been attributed to the expanded use of antibiotics and the growing number of patients who are coinfected with HIV. In recent years, there has been a remarkable increase in the incidence of NS in China [4].…”
Section: Introductionmentioning
confidence: 99%
“…Tertiary syphilis can present as gummatous skin and mucosal lesions, as well as involves cardiovascular and neurologic systems (Schoutens et al 1996 ;Chudomirova et al 2009 ). Skin lesions are solitary or multiple and consist of superfi cial nodular and deep gummatous subtypes.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Benign gummatous syphilis shows granulomatous infl ammation with central zones of acellular necrosis in involved organs. In cutaneous lesions, blood vessels throughout the dermis and subcutaneous fat exhibit endarteritis obliterans, with variable angiocentric plasma cell infi ltrates (Schoutens et al 1996 ;Wu et al 2000 ;Rocha et al 2004 ;Chudomirova et al 2009 ).…”
Section: Tertiary Syphilismentioning
confidence: 99%